PROBLEMS THAT ARISE IN TRANSLATING TEXTS FROM ENGLISH INTO OTHER LANGUAGES - F.T.Boysriyeva, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This article examines the major linguistic, cultural, and structural difficulties that occur when translating texts from English into other languages. The study focuses on semantic ambiguity, polysemy, idiomatic expressions, cultural references, syntactic differences, and lexical gaps. It also highlights the challenges caused by genre-specific features, technological limitations, and translator competence. The paper emphasizes the importance of contextual analysis, cultural awareness, and modern translation technologies in improving translation quality. Practical methodological recommendations are offered for translators and language instructors.